한국 남성 비알코올성 지방간에서 혈청 adipokine 농도 변화에 영향을 미치는 요인 - 오세용; Se Yong Oh; 조용균; Yong Kyun Cho; 유태우; Tae Woo Yoo; 박정호; Jung Ho Park; 김홍주; Hong Joo Kim; 박동일; Dong Il Park; et al. (The Korean journal of medicine, 2006)
목적: Adipokine은 인슐린 저항성, 비만 그리고 이상 지질혈증 등의 다양한 대사질환과 관련이 있다. 또한 대사질환은 비알코올성 지방간질환과의 연관성이 알려져 있다. 저자들은 비알코올성 지방간질환에서 지방간 정도에 따른 혈청 adipokine 농도 변화와 혈청 adipokine 농도 변화에 영향을 미치는 독립적 위험인자를 알아보고자 하였다. 방법: 한국 정상 성인 남자 65명을 대상으로 하였으며, 지방간 정도는 초음파에서 관찰되는 소견에 따라 Group I: 정상간(27명), Group II: 경도 지방간(24명), Group III: 중등도 이상의 지방간(14명) 세 군으로 분류하였다. 모든 대상자로부터 신체계측지표와 leptin, adiponectin 그리고 resistin의 공복 혈청 농도를 측정하였다. 인슐린 저항성은 HOMA-IR를 사용하여 평가하였다. 결과: 혈청 leptin 농도는 세 군 간에 유의한 차이가 있었다(평균±표준편차: Group I (2.052±1.071), Group II (2.879±1.016), Group III (4.457±1.965 ng/mL), p<0.001). 혈청 adiponectin과 resistin 농도는 세 군 간에 유의한 차이가 없었다(각각 p=0.184, p=0.649). 체질량지수와 HOMA-IR은 혈청 leptin 농도 변화에 대한 독립적 위험인자 이었으나(각각 p=0.026, p=0.001), 혈청 adiponectin과 resistin 농도 변화에 대한 독립적 위험인자는 관찰할 수 없었다. 결론: 본 연구에서 leptin은 비알코올성 지방간질환의 발생기전에 대사장애를 유도함으로써 간접적으로 관여함을 알 수 있었다. 그러나 adiponectin과 resistin은 비알코올성 지방간질환의 발생기전에 관련성이 있는지 알 수 없었다. 체질량지수와 HOMA-IR만이 혈청 leptin농도 변화에 대한 독립적 위험인자 이었다. Background: Adipokines are associated with various metabolic disorders including insulin resistance, obesity and dyslipidemia. Metabolic disorders have also been reported to be associated with nonalcoholic fatty liver disease (NAFLD). We aimed to estimate changes in serum adipokines levels according to the degrees of steatosis and to determine independent factors influencing serum adipokines levels in Korean male patients with NAFLD. Methods: 65 Korean male patients were subjected. The degrees of steatosis were stratified into the three groups, Group I: normal liver (27 subjects), Group II: mild fatty liver (24 subjects) and Group III: moderate to severe fatty liver (14 subjects), according to ultrasonographic liver findings. The anthropometric parameters, fasting serum adipokine levels including leptin, adiponectin and resistin were measured in all subjects. The level of insulin resistance was estimated using the HOMA-IR. Results: Serum leptin levels were significantly different among the three groups (mean±SD: Group I (2.052±1.071), Group II (2.879±1.016), Group III (4.457±1.965 ng/mL), p<0.001). Serum adiponectin and resistin levels were not significantly different among the three groups (p=0.184, p=0.649, respectively). BMI and HOMA-IR were independent factors of changes in serum leptin levels (p=0.026, p=0.001, respectively), but independent factors of changes in serum adiponectin and resistin levels were not observed. Conclusions: Our study support a indirect role to induce metabolic disorder for leptin in the pathogenesis of NAFLD, but do not support roles for adiponectin and resistin in the pathogenesis of NAFLD. BMI and HOMA-IR were only independent factors of changes in serum leptin levels.(Korean J Med 71:58-66, 2006)